Reducing antibiotic use for uncomplicated urinary tract infection in general practice by treatment with uva-ursi (REGATTA) - a double-blind, randomized, controlled comparative effectiveness trial - Kambiz Afshar; Nina Fleischmann; Guido Schmiemann; Jutta Bleidorn; Eva Hummers-Pradier; Tim Friede; Karl Wegscheider; Michael Moore; Ildikó Gágyor (BMC, 2018)
Abstract Background Uncomplicated urinary tract infections (UTI) are common in general practice and usually treated with antibiotics. This contributes to increasing resistance rates of uropathogenic bacteria. A previous trial showed a reduction of antibiotic use in women with UTI by initial symptomatic treatment with ibuprofen. However, this treatment strategy is not suitable for all women equally. Arctostaphylos uva-ursi (UU, bearberry extract arbutin) is a potential alternative treatment. This study aims at investigating whether an initial treatment with UU in women with UTI can reduce antibiotic use without significantly increasing the symptom burden or rate of complications. Methods This is a double-blind, randomized, and controlled comparative effectiveness trial. Women between 18 and 75 years with suspected UTI and at least two of the symptoms dysuria, urgency, frequency or lower abdominal pain will be assessed for eligibility in general practice and enrolled into the trial. Participants will receive either a defined daily dose of 3 × 2 arbutin 105 mg for 5 days (intervention) or fosfomycin 3 g once (control). Antibiotic therapy will be provided in the intervention group only if needed, i.e. for women with worsening or persistent symptoms. Two co-primary outcomes are the number of all antibiotic courses regardless of the medical indication from day 0-28, and the symptom burden, defined as a weighted sum of the daily total symptom scores from day 0-7. The trial result is considered positive if superiority of initial treatment with UU is demonstrated with reference to the co-primary outcome number of antibiotic courses and non-inferiority of initial treatment with UU with reference to the co-primary outcome symptom burden. Discussion The trial's aim is to investigate whether initial treatment with UU is a safe and effective alternative treatment strategy in women with UTI. In that case, the results might change the existing treatment strategy in general practice by promoting delayed prescription of antibiotics and a reduction of antibiotic use in primary care. Trial registration EudraCT: 2016-000477-21. Clinical trials.gov: NCT03151603 (registered: 10 May 2017).